2022
DOI: 10.1039/d1me00119a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of COVID-19 therapeutics: luteolin as an allosteric modulator of the spike protein of SARS-CoV-2

Abstract: The interactions between the receptor binding domain (RBD) of SARS-CoV-2 and the angiotensin- converting enzyme 2 (ACE2) are crucial for viral entry and subsequent replication. Given the large and featureless...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In addition, luteolin inhibits the activities of the main protease (Chaves et al, 2022) and RNA‐dependent RNA polymerase (Munafò et al, 2022) of SARS‐CoV‐2, leading to the inhibition of viral replication in vivo. In addition to experimental reports, more than 70 articles (Alvarado et al, 2022; Shadrack et al, 2021) predicted that luteolin can interact with the S‐protein‐ACE2 complex or combine with other important proteins of SARS‐CoV‐2 by virtual screening methods. Overall, these findings suggested that luteolin is a promising natural compound for the treatment and management of SARS‐CoV‐2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, luteolin inhibits the activities of the main protease (Chaves et al, 2022) and RNA‐dependent RNA polymerase (Munafò et al, 2022) of SARS‐CoV‐2, leading to the inhibition of viral replication in vivo. In addition to experimental reports, more than 70 articles (Alvarado et al, 2022; Shadrack et al, 2021) predicted that luteolin can interact with the S‐protein‐ACE2 complex or combine with other important proteins of SARS‐CoV‐2 by virtual screening methods. Overall, these findings suggested that luteolin is a promising natural compound for the treatment and management of SARS‐CoV‐2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…It represents an urgent need for an effective medical intervention strategy to avoid further social and economic consequences ( Hu et al, 2021 ). Different types of vaccines, for example, those from Pfizer-BioNTech or Moderna using the mRNA of spike (S) protein, are currently available, and there are several FDA approved drug candidates under consideration ( Li et al, 2021 ; Venkadapathi et al, 2021 ; Alvarado et al, 2022 ). At the same time, more infectious mutants such as B.1.617.2 (Delta), B.1.427/B.1.429 (Epsilon), and more recently Omicron have appeared ( McCallum et al, 2021 ; Cao et al, 2022 ), and some evade from the immune system ( Yurkovetskiy et al, 2020 ; Harvey et al, 2021 ; Wang et al, 2021 ; Gobeil et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have previously identified residues important to either drug binding, allosteric effects, or both, for the S protein. According to work by Alvarado et al, LYS369 and PHE377 appeared to have important allosteric properties since binding of luteolin to these residues in the S protein induced an intense allosteric effect [13]. Verkhivker et al reported that GLU406, ASN439, LYS417 and ASN501 were centers of allosteric interactions implicated in mediating long-range communications in the binding of the S protein with ACE2 [14].…”
Section: Resultsmentioning
confidence: 99%
“…Dihedral angle values vs. time for residues identified in literature as either important to allostery or the formation of a druggable pocket: a) PHE 377 chain C phi [13], b) PHE 329 chain B psi [8], c) ASP 198 chain C psi [15], d) ASN 439 chain A psi [14]. Dihedral angle values vs. time for most other residues: e) PRO 39 chain A phi, f) ILE 332 chain B psi.…”
Section: Resultsmentioning
confidence: 99%